If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(h + 5)(h) = 18 Reorder the terms: 0.5(5 + h)(h) = 18 Reorder the terms for easier multiplication: 0.5h(5 + h) = 18 (5 * 0.5h + h * 0.5h) = 18 (2.5h + 0.5h2) = 18 Solving 2.5h + 0.5h2 = 18 Solving for variable 'h'. Reorder the terms: -18 + 2.5h + 0.5h2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 2.5h + 0.5h2 = 0 Begin completing the square. Divide all terms by 0.5 the coefficient of the squared term: Divide each side by '0.5'. -36 + 5h + h2 = 0 Move the constant term to the right: Add '36' to each side of the equation. -36 + 5h + 36 + h2 = 0 + 36 Reorder the terms: -36 + 36 + 5h + h2 = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 5h + h2 = 0 + 36 5h + h2 = 0 + 36 Combine like terms: 0 + 36 = 36 5h + h2 = 36 The h term is 5h. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5h + 6.25 + h2 = 36 + 6.25 Reorder the terms: 6.25 + 5h + h2 = 36 + 6.25 Combine like terms: 36 + 6.25 = 42.25 6.25 + 5h + h2 = 42.25 Factor a perfect square on the left side: (h + 2.5)(h + 2.5) = 42.25 Calculate the square root of the right side: 6.5 Break this problem into two subproblems by setting (h + 2.5) equal to 6.5 and -6.5.Subproblem 1
h + 2.5 = 6.5 Simplifying h + 2.5 = 6.5 Reorder the terms: 2.5 + h = 6.5 Solving 2.5 + h = 6.5 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + h = 6.5 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + h = 6.5 + -2.5 h = 6.5 + -2.5 Combine like terms: 6.5 + -2.5 = 4 h = 4 Simplifying h = 4Subproblem 2
h + 2.5 = -6.5 Simplifying h + 2.5 = -6.5 Reorder the terms: 2.5 + h = -6.5 Solving 2.5 + h = -6.5 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + h = -6.5 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + h = -6.5 + -2.5 h = -6.5 + -2.5 Combine like terms: -6.5 + -2.5 = -9 h = -9 Simplifying h = -9Solution
The solution to the problem is based on the solutions from the subproblems. h = {4, -9}
| 2x^3+6x=-7x^2 | | 6(b-4)=30 | | 25=.5(h*h+8) | | (-11x^2y^2)(-6xy^5)= | | 6x^2+17x+7= | | 3a^3-36a^2+81a=0 | | 3x^2+7X-15=0 | | (3x)(-2x^5)= | | 4x^0y= | | 6(6x-7)(3x+7)=0 | | -37+(-48)=d | | 9y-4x=12 | | -8(x+3)=8-7x | | 4m^2+7m=25 | | -2(4x-3)=4x | | 6x^2+9x-2=0 | | (2x+1)(4x^2+27X-0)= | | 2s^2-32s=56 | | 16=i^2(4) | | 5x^2+9x-7=0 | | 5[7-5(6-y)]-7=7[5(7y-6)+4]-50 | | 5[7-5(-y)]-7=7[5(7y-6)+4]-50 | | 3x^2+24x=48 | | x^3-5x^2+16x-80=0 | | 2.8=7.6+y | | 22x-4-18x=2(2x-4)+4 | | 5r^2=2r | | 7[9-7(8-b)]-9=9[(9b-8)+6]-82 | | 4x+9+x=24 | | 3.5x+2.75=10 | | 3*10/6= | | 3x+8-7x=15-16x+12x-7 |